Why airplanes crash : aviation safety in a changing world - Oster, Clinton V. (Oxford University Press, 1992)
The authors discuss what private and public policies can do to increase airline safety in an age of the deregulation of commercial airlines. The book compares the US experience with aviation in other countries, especially Canada. Then it examines the three safety issues: the safety margin that allows for human error and equipment failure; the worldwide ageing of all airline fleets; and terrorism and sabotage.